2014
DOI: 10.1371/journal.pone.0103523
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Children with Acute Hematogenous Osteomyelitis Caused by Methicillin-Resistant Staphylococcus aureus: Correlation with Clinical Severity of Illness

Abstract: Children with acute hematogenous osteomyelitis (AHO) demonstrate a broad spectrum of clinical manifestations, ranging from mild to severe. Several advances have been achieved in the study of host immune response to acute invasive Staphylococcus aureus infections through gene expression analysis. However, previous research has neither attempted to evaluate the response of children with AHO specific to Methicillin-resistant Staphylococcus aureus (MRSA) nor to correlate gene expression with clinical phenotype. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The pathogenetic mechanisms underlying the variation of clinical manifestations of children with osteomyelitis due to MRSA are incompletely understood. We have previously reported that children with invasive MRSA infections display an over-expression of innate immunity and under-expression of adaptive immunity and that specific genes correlate with severity of illness [ 32 ]. Although host factors are likely to play a role in clinical variability, attention must still be directed to the bacteria in light of the diverse virulence capabilities of MRSA.…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenetic mechanisms underlying the variation of clinical manifestations of children with osteomyelitis due to MRSA are incompletely understood. We have previously reported that children with invasive MRSA infections display an over-expression of innate immunity and under-expression of adaptive immunity and that specific genes correlate with severity of illness [ 32 ]. Although host factors are likely to play a role in clinical variability, attention must still be directed to the bacteria in light of the diverse virulence capabilities of MRSA.…”
Section: Resultsmentioning
confidence: 99%
“…[51][52][53]) or 5 on Staphylococcus aureus infection (e.g. [54,55]). Notably considerable interest has also emerged recently over the use of blood transcriptomic platforms for the profiling of in vivo responses to vaccines (e.g.…”
Section: Blood Transcriptome Profiling Studies In Health and Diseasementioning
confidence: 99%
“…Although platelets are not a laboratory measure that is routinely followed for AHO disease monitoring, upregulation of platelets can help distinguish between patients with and without the disease 16. An upregulation of innate immunity, including platelets, has been found in patients with MRSA AHO 17. Furthermore, Panton-Valentine leucocidin–positive Staphylococcus aureus strains have been linked to thrombosis in AHO, which is likely activated by Panton-Valentine leucocidin–damaged neutrophils 18.…”
Section: Discussionmentioning
confidence: 99%